I'll do the first one to get you started
--------------------------------------
The equation x^2 + x - 6 = 0 is the same as 1x^2 + 1x + (-6) = 0. It is in the form ax^2 + bx + c = 0
We see that a = 1, b = 1, c = -6. Those values will be plugged into the quadratic formula (see attached image for steps).
The answers are x = -3 and x = 2. The order of the roots does not matter.
--------------------------------------
To factor 1x^2 + 1x - 6, we need to find two numbers such that they add to 1 (the x coefficient) and multiply to -6 (the constant term)
Two such numbers are 3 and -2. This is found through trial and error.
Note how 3 plus -2 = 1 and 3 times -2 = -6.
So x^2 + x - 6 = 0 becomes (x+3)(x-2) = 0. You can use the FOIL rule to get x^2+x-6 back again.
Now use the zero product property to solve
(x+3)(x-2) = 0
x+3 = 0 or x-2 = 0
x = -3 or x = 2
which are the two solutions we got when we used the quadratic formula.